PENDEDERAN LARVA IKAN TAMBAKAN (Helostoma temmincki) DENGAN PADAT TEBAR BERBEDA - Joko, Joko; Muslim, Muslim; HT, Ferdinand (Jurnal Perikanan dan Kelautan, 2013)
The aimed of this research was to find out survival rate and growth of kissinggouramy larvae with different stocking density. Research used Completely RandomizedDesign (CRD) with five treatments and three replications. The treatment was useddifferent of stocking density were 6, 8, 10, 12, and 14 larvae per liter. Result of researchshowed that the different of stocking density was significant on length and weightgrowth, but not significant for survival rate. Stocking density with six larvae per literwas resulted the highest value consist of absolute length growth (3.2±0.0 cm per larvae),absolute weight growth (476.67±11.55 mg per larvae) and survival rate (60.55±1.27 %).Physical-Chemical parameters of water during research was in optimal range weretemperature 26-280C, pH 6.9-7.1, dissolved oxygen 4.00-4.09 mg.L-1 and ammonia0.004–0.013 mg.L-1.